2021
DOI: 10.1186/s13014-021-01952-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical patient-specific pre-treatment quality assurance with the new helical tomotherapy platform, following the AAPM TG-218 report

Abstract: Purpose This study presents patient-specific quality assurance (QA) results from the first 395 clinical cases for the new helical TomoTherapy® platform (Radixact) coupled with dedicated Precision TPS. Methods The passing rate of the Gamma Index (GP%) of 395 helical QA of patient-specific tomotherapy, acquired with ArcCHECK, is presented, analysed and correlated to various parameters of the plan. Following TG-218 recommendations, the clinic specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The plan parameters of HT that have a statistically significant influence on the pass/failure of pre-treatment QA were examined in conjunction with TomoEQA. The results are relatively consistent with those of previous research [ 28 31 ]. The findings of this study, including dose inaccuracy in the off-axis region, are considered to be a result of the thread effect.…”
Section: Discussionsupporting
confidence: 93%
“…The plan parameters of HT that have a statistically significant influence on the pass/failure of pre-treatment QA were examined in conjunction with TomoEQA. The results are relatively consistent with those of previous research [ 28 31 ]. The findings of this study, including dose inaccuracy in the off-axis region, are considered to be a result of the thread effect.…”
Section: Discussionsupporting
confidence: 93%
“…demonstrated that AL and TL need to be regularly adjusted as the number of cases increases and new technologies are introduced. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The number of cases analyzed also had an important impact on the results; Fusella et al demonstrated that AL and TL need to be regularly adjusted as the number of cases increases and new technologies are introduced. 23 We conducted an analysis of %GP, which facilitated rapid evaluation of PSQA results. However, numerous studies also recommend considering additional clinically relevant factors, such as the correlation between the patient planning structure and the point of gamma analysis failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 , 16 The dataset used in this work is an extension of the one used in Ref. [ 17 ]. The treatments were related to different sites and diseases.…”
Section: Methodsmentioning
confidence: 99%